Catalyst- and Metal-Free Rapid Functionalizations of Alkynes Using TsNBr2 - Chawla, Ruchi; Singh, Atul K.; Yadav, Lal Dhar S. (Synlett, 2013)
A very rapid (3–12 min) and efficient method has been developed for a one-pot synthesis of α,α-dibromoalkanones and β-bromoenol alkanoates directly from alkynes using N,N-dibromo-p-toluenesulfonamide (TsNBr2). The protocol is embellished with features like ambient temperature, high regioselectivity, operational simplicity, and metal- and catalyst-free conditions.
Keywords: alkynes; TsNBr2; α,α-dibromoalkanones; β-bromoenol alkanoates; catalyst-free conditions